An Integrated Pharmacological Counselling Approach to Guide Decision-Making in the Treatment with CDK4/6 Inhibitors for Metastatic Breast Cancer - Rossana Roncato; Lorenzo Gerratana; Lorenza Palmero; Lorenza Palmero; Sara Gagno; Ariana Soledad Poetto; Elena Peruzzi; Martina Zanchetta; Bianca Posocco; Elena De Mattia; Giovanni Canil; Martina Alberti; et al. (Frontiers Media S.A., 2022)
A wide inter-individual variability in the therapeutic response to cyclin-dependent kinases 4 and 6 inhibitors (CDKis) has been reported. We herein present a case series of five patients treated with either palbociclib or ribociclib referred to our clinical pharmacological counselling, including therapeutic drug monitoring (TDM), pharmacogenetics, and drug-drug interaction analysis to support clinicians in the management of CDKis treatment for metastatic breast cancer. Patients' plasma samples for TDM analysis were collected at steady state and analyzed by an LC-MS/MS method for minimum plasma concentration (Cmin) evaluation. Under and overexposure to the drug were defined based on the mean Cmin values observed in population pharmacokinetic studies. Polymorphisms in selected genes encoding for proteins involved in drug absorption, distribution, metabolism, and elimination were analyzed (CYP3A4, CYP3A5, ABCB1, SLCO1B1, and ABCG2). Three of the five reported cases presented a CDKi plasma level above the population mean value and were referred for toxicity. One of them presented a low function ABCB1 haplotype (ABCB1-rs1128503, rs1045642, and rs2032582), possibly causative of both increased drug oral absorption and plasmatic concentration. Two patients showed underexposure to CDKis, and one of them was referred for early progression. In one patient, a CYP3A5*1/*3 genotype was found to be potentially responsible for more efficient drug metabolism and lower drug plasma concentration. This intensified pharmacological approach in clinical practice has been shown to be potentially effective in supporting prescribing oncologists with dose and drug selection and could be ultimately useful for increasing both the safety and efficacy profiles of CDKi treatment.